Microwave-assisted conversion of palm kernel shell biomass waste to photoluminescent carbon dots - Ang, Wei Lun (Sci Rep, 2020)
In the present work, palm kernel shell (PKS) biomass waste has been used as a low-cost and easily available precursor to prepare carbon dots (CDs) via microwave irradiation method. The impacts of the reacting medium: water and diethylene glycol (DEG), and irradiation period, as well as the presence of chitosan on the CDs properties, have been investigated. The synthesized CDs were characterized by several physical and optical analyses. The performance of the CDs in terms of bacteria cell imaging and copper (II) ions sensing and removal were also explored. All the CDs possessed a size of 6–7 nm in diameter and the presence of hydroxyl and alkene functional groups indicated the successful transformation of PKS into CDs with carbon core consisting of C = C elementary unit. The highest quantum yield (44.0%) obtained was from the CDs synthesised with DEG as the reacting medium at irradiation period of 1 min. It was postulated that the high boiling point of DEG resulted in a complete carbonisation of PKS into CDs. Subsequently, the absorbance intensity and photoluminescence intensity were also much higher compared to other precursor formulation. All the CDs fluoresced in the bacteria culture, and fluorescence quenching occurred in the presence of heavy metal ions. These showed the potential of CDs synthesised from PKS could be used for cellular imaging and detection as well as removal of heavy metal ions.